Pulmonary haemorrhage due to an aortopulmonary collateral artery after arterial switch. (6th July 2015) - Sugimoto, Ai; Ota, Noritaka; Sakamoto, Kisaburo
Abstract: A neonate with transposition of the great arteries and intact ventricular septum presented without pulmonary over-circulation, and subsequently developed pulmonary haemorrhage after corrective surgery. Postoperative CT revealed an aortopulmonary collateral artery arising from the descending aorta, and we performed successful embolisation on postoperative day 9. Aggressive imaging modalities such as angiography and/or CT imaging with contrast can detect unexpected extra-pulmonary blood supply and guide further management.